2007
DOI: 10.1021/ma0627572
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Tensile-Deformed High-Density Polyethylene during Annealing:  Scanning Synchrotron Small-Angle X-ray Scattering Study

Abstract: The structural evolution of high-density polyethylene subjected to uniaxial tensile deformation was investigated as a function of strain and after annealing at different temperatures using a scanning synchrotron small-angle X-ray scattering (SAXS) technique. The results confirm that in the course of tensile deformation intralamellar block slips were activated at small deformations followed by a stress-induced fragmentation and recrystallization process yielding thinner lamellae with their normal parallel to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 38 publications
4
113
0
Order By: Relevance
“…As discussed in our previous investigations, for a semiquantitative discussion of the dependence of the long spacing on the strain, the type of data treatment (Lorentz correction versus no correction) plays only a subordinate role. [26][27][28] Consequently, Lorentz-corrected scattering curves were applied in the present work to evaluate the microstructural parameters. The average thicknesses of the crystalline lamellae and amorphous layers measured along the stretching direction can be derived from the one-dimensional electron density correlation function K(z) as follows: [41][42][43][44][45] …”
Section: In Situ Saxs Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in our previous investigations, for a semiquantitative discussion of the dependence of the long spacing on the strain, the type of data treatment (Lorentz correction versus no correction) plays only a subordinate role. [26][27][28] Consequently, Lorentz-corrected scattering curves were applied in the present work to evaluate the microstructural parameters. The average thicknesses of the crystalline lamellae and amorphous layers measured along the stretching direction can be derived from the one-dimensional electron density correlation function K(z) as follows: [41][42][43][44][45] …”
Section: In Situ Saxs Resultsmentioning
confidence: 99%
“…The characteristics of the evolution of the microstructure in the systems during stretching follow a common scheme as discussed before for isotropic semicrystalline polymers. 27,28,40 Figure 13 presents the variation of SAXS diagrams with strain for the skin layers of micro-molded mixtures. As can be seen, the SAXS pattern shows a highly anisotropic scattering distribution prior to deformation indicating an oriented lamellar structure along the flow direction.…”
Section: Scanning Saxs Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 As the cubic cluster units are assumed to be rigid, the current model has no ability to describe the changes in long spacing and lamellar thickness. The compression of cubic cluster units and deformation within the cubic units may need to be taken into account under close packing and rearrangement of cubic units during necking.…”
Section: Application Of Catastrophe Theory K-h Nitta and M Kuriyagawamentioning
confidence: 99%
“…Influence of deformation temperature on structural variation and shape-memory effect of a thermoplastic semi-crystalline multiblock copolymer The deformation temperature (T deform ) has significant effects on deformation behaviors of semi-crystalline polymers on the microscopic and macroscopic scale [9,10], with structural variations during the deformation playing a dominant role in determining their mechanical properties [11,12]. It also has been reported that T deform can affect the SME of semicrystalline MBCs, i.e., if the samples are deformed at a temperature lower than the thermal transition temperature (T trans ) of switching domains, reduction in fixity ratio (R f ) and switching temperature (T sw ) can be observed as well as a higher maximum stress (!…”
mentioning
confidence: 99%